STUDI FENOMENOLOGI : PENGALAMAN KELUARGA DALAM MERAWAT ANGGOTA KELUARGA YANG MENGALAMI GANGGUAN JIWA - Lilik Setiawan (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2018)
Current mental disorders have become a global health problem. People with mental disorders may not be able to overcome their own psychological problems. People with mental disorders need support from other people, especially families as people who care for people with mental disorders or also called caregivers. Every family in caring for people with mental disorders will face a different experience between one family and another. Experience will greatly affect how a person perceives something that is felt, the perception that is not only determined by the objective stimulus, but also influenced by the circumstances of the perceptor. The purpose of this study was to find the family experience in caring for family members who experience mental disorders in the Puhjarak Health Center Work Area District of Plemahan, Kediri Regency. The research design was used qualitative research with a phenomenological descriptive approach. Data collection was used in-depth interview method using semi-structured interview guides involving five participants, then analyzed using Colaizzi model data analysis techniques. This study produced seven themes including: Feeling not too important to be treated, Feeling desperate in caring for clients , Performing client care according to ability, Utilizing health facilities, Feeling having heavy responsibilities, Unfavorable economic situation, and Negative attitudes from other family members. In this study, the family has carried out family tasks in the health care even though limited to their ability. During family care, they feel that they have heavy responsibilities and feeling despair because of the very complex problems that family face when taking care. Keywords: Experience, Family, Mental Disorder